2010
DOI: 10.1007/s10764-010-9396-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Robotic Approaches in Primate Gait Analysis

Abstract: Understanding how primates move is particularly challenging because many of the experimentation techniques that would normally be available are unsuitable for ethical and conservation reasons. We therefore need to develop techniques that can maximize the data available from minimally intrusive experimentation. One approach for achieving this is to use evolutionary robotic techniques to build a musculoskeletal simulation and generate movement patterns that optimize some global parameter such as economy or perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 65 publications
1
41
0
Order By: Relevance
“…Recently, both Sellers et al (2010) and Crompton et al (2010) suggested that evidence for a lengthy Achilles tendon may be found in the trabecular microarchitecture underlying the Achilles insertion. We agreed with these authors that studying the Achilles tendon's effect on trabeculae was an appropriate approach and attempted to test this hypothesis in a small sample of primates; however, our study failed to find any correlation between Achilles tendon morphology and parameters of trabecular microstructure in the region underlying the Achilles tendon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, both Sellers et al (2010) and Crompton et al (2010) suggested that evidence for a lengthy Achilles tendon may be found in the trabecular microarchitecture underlying the Achilles insertion. We agreed with these authors that studying the Achilles tendon's effect on trabeculae was an appropriate approach and attempted to test this hypothesis in a small sample of primates; however, our study failed to find any correlation between Achilles tendon morphology and parameters of trabecular microstructure in the region underlying the Achilles tendon.…”
Section: Discussionmentioning
confidence: 99%
“…The Achilles tendon is comprised of the triceps surae muscle complex merging distally to form a single tendon, which inserts onto the tuber of the calcaneus (O'Brien, 2005;Harris and Peduto, 2006). The Achilles tendon has been found to increase locomotor efficiency by storing energy and returning it in elastic recoil (Alexander and BennetClark, 1977;Alexander, 1984;Ker et al, 1987;Swartz, 1993;Sellers et al, 2010) and is subject to extremely high loads during various activities such as walking, running, and jumping (O'Brien, 2005). Because the Achilles tendon is particularly efficient at storing elastic energy during running, some (e.g., Bramble and Lieberman, 2004) have argued that an elongated tendon was a crucial adaptation that allowed for long distance endurance running in early members of the genus Homo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), the GRFs were visually and quantitatively less realistic than other simulated variables. Other predictive simulations of human running have had similar issues with short stance times [41,42]. The model is capable of generating more realistic GRF with its existing dynamics, as seen in the data-tracking simulation (figure 3).…”
mentioning
confidence: 87%
“…In recent simulation work (Sellers et al 2010), the role of tendon elasticity was quantified by 'virtual ablation'. In this paradigm, simulations are repeated with identical anatomical models except for the structure of interest, which is c h i m p a n z e e g o r i l l a o r a n g u t a n g i b b o n h u m a n r e i n d e e r h a r e g r e y h o u n d Review.…”
mentioning
confidence: 99%